Survival and Reproductive Response of Adult Rabbits Exposed to Graded Levels of Crude Oil Contaminated Diets - Yahaya, M.A.; Aruwayo, A. (Pakistan Journal of Nutrition, 2014)
A study was conducted to establish the survival and reproductive response of adults rabbits exposed to graded levels of crude oil contaminated diet. Thirty two rabbits of mixed breed of New Zealand White and Chinchilla were used in this study. The study entailed four treatment groups (designated) A, B, C and D with eight rabbits of equal sex ratio replicated four times were randomly assigned to each group. The levels of crude oil inclusion in the diet were 0.00%, (control A) 0.01, 0.02 and 0.03% for treated groups B, C and D respectively. The study lasted for fourteen weeks. There was no significant difference (p>0.05) in weight gain among the groups. The mean feed intake, average weekly body weight gain as well as final body weight were not significantly different (p>0.05) amongst the group. There was no mortality recorded at the highest inclusion rate of 0.03% in this study. Results obtained on the reproductive response revealed 68% were pregnant including the control group and 50% conception rate was recorded amongst the experimental groups. Therefore, it could be concluded that, the adult rabbits were able to survive, conceive and kindle at the highest crude oil inclusion rate of 0.03%, without any adverse effect on the experimental rabbits, hence establishing their survival level and reproductive capability of adults rabbits exposed to crude oil contamination.